Evangeliserende gemeente: n Leefwyse? n Besinning oor missionere gerigtheid as aspek van gemeentewees - Swanepoel, P. C. (Hervormde teologiese studies, 1996)
Evangelising community: A life style?. The church finds itself in a crisis. The essence of this crisis manifests itself in the fact that the church has forgotten its vocation to be an evangelising church. There are, however, a multitude of factors which hamper the church in the fulfillment of its mission. This crisis, however, need not paralyse the church, but should be seen as a challenge for the community of Christ to become an evangelising community.